The queen's accomplice - MacNeal, Susan Elia (MacNeal, Susan Elia. Maggie Hope mystery., 2016)
"This New York Times bestselling mystery series continues as American-born codebreaker extraordinaire, Maggie Hope, returns to England to continue her intelligence work during World War II. England, 1942. Great Britain and the U.S. have joined forces to fight the Nazis. In London, Maggie Hope takes on the biggest challenge of her career: finding a killer who models himself on Jack the Ripper--and who targets female intelligence agents...like Maggie"--